Developing of an open-source toolbox for liquid-vapor phase change in the porous wick of a LHP evaporator based on OpenFOAM. (July 2022) - Wang, H.J.; Xu, J.Y.; Hong, F.J.
Abstract: The deep understanding of characteristics and mechanism of liquid-vapor phase change and capillary pumping in porous wick is necessary for the optimal design of efficient heat transfer devices such as loop heat pipes. This paper develops a toolbox based on OpenFOAM for simulating the two-phase flow and phase change heat transfer in the hybrid domain using the micro-continuum model, which can asymptotically converge to Darcy model in porous domain and NS equation in solid-free domain. The toolbox also provides choices for the phase change model, capillary pressure model, and specific boundary conditions. The toolbox is validated by comparing the simulation results with analytical solutions or published results through several example problems. The simulation of the LHP evaporator indicates the receding of liquid-vapor interface into the porous wick with the increasing of heat flux, and its thermal performance is in good agreement with previous experimental studies. The developed toolbox can be anticipated to do theoretical and optimized studies on phase change heat transfer in porous media.